CHEILOSCOPY: STUDY OF PATTERN OF LIP PRINTS AMONG MBBS STUDENTS - MERRY PAL KAUR CHAWLA; KULDIP KUMAR; GAURAV AGNIHOTRI; JASPINDER PRATAP SINGH; AASHISH SHARMA; NEHA CHAUDHARY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study was conducted to classify and evaluate the patterns of lip prints and their variations in adult population. Methods: The study was conducted on 200 MBBS students of age group of 18–23 years at the Department of Forensic Medicine and Toxicology, Amritsar, including 100 males and 100 females. Lip color was applied on lips, and lip prints were taken using a strip of cellophane tape on its glued portion. Data thus obtained were compiled, scrutinized, and analyzed to find different patterns. Lip prints of each subject were divided into four quadrants and recognized as per Suzuki and Tsuchihashi’s Classification. Results: The most common type of lip print pattern among 200 subjects was found to be Type III 28.37% cases, which was followed by Type I 19.75% cases, this was followed by Type I’ and Type IV 16.25% cases each. Type II was in 14.87% cases. The least common type of lip print pattern was found to be Type V in 4.5% cases. Conclusion: The study concluded type III to be the most predominant pattern overall in the study population. There was no gender differentiation seen with respect to both sexes as the type III pattern was found most prevalent in both females and males.